2020
DOI: 10.1111/fcp.12529
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of hemin in isoprenaline‐induced myocardial infarction: role of ATP‐sensitive potassium channel and endothelial nitric oxide synthase

Abstract: A B S T R A C TIschemic heart disease is a common cardiac health problem. Despite the significant advances in prevention and treatment of this disorder, its incidences and complications are very serious. So, the search for more antioxidants and anti-inflammatory agents with cardioprotective effects is an urgent task. We aimed to evaluate the effects of a heme oxygenase 1 (HO1) inducer, hemin (HEM), on isoprenaline (ISO)induced myocardial damage. Forty-five Wistar albino rats were used. Animals were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The capacity of those antioxidants is evaluated via the detection of TAC reflecting the balance between oxidants and antioxidants. 54,55 The present data showed that TCA decreased the serum TAC level; this is in agreement with Fouad et al, 2017. 56 Cytokines especially IL-1 are so important in initiation and the progression of hepatic carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…The capacity of those antioxidants is evaluated via the detection of TAC reflecting the balance between oxidants and antioxidants. 54,55 The present data showed that TCA decreased the serum TAC level; this is in agreement with Fouad et al, 2017. 56 Cytokines especially IL-1 are so important in initiation and the progression of hepatic carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…Reactive oxygen species (ROS)-induced injury plays an important role in the development of myocardial I/ R [38,39]. During reperfusion, the blood supply of the tissues triggers the 'explosion' of oxygen free radicals; hence, the accumulated ROS attack the cells and cause damage.…”
Section: Discussionmentioning
confidence: 99%
“…These effects promoted an increase in cardiac tolerance to I/R. There is evidence that bradykinin, adenosine, opioids, cannabinoids, urocortin, natriuretic peptides, hemin, and melatonin result in KATP channel opening [271][272][273][274][275][276][277]. These compounds enhance cardiac tolerance to I/R and are involved in preconditioning and postconditioning [119,[273][274][275].…”
Section: Katp Channels and Pkcmentioning
confidence: 99%